Legal Analysis of Medical Malpractice Cases Based On Supreme Court Decision Number 85/Pdt/2021/PT.PAL - Afwan Ridha; Dafrinaldi; Muhammad Hatta; Ikramsyah Irwali (International Journal of Law, Social Science, and Humanities, 2026)
This study examines the legal aspects of Supreme Court Decision Number 85/Pdt/2021/PT.PAL relating to alleged medical malpractice in Indonesia. The research focuses on analysing the judges' legal considerations, the application of medical professional standards, and the forms of legal liability of medical personnel from civil, criminal, and professional perspectives. The research uses a normative legal method with a case approach and a statute approach. The results show that in the decision, the judge applied the prudence principle and the lex artis ad hoc doctrine, which is the assessment of medical actions based on professional standards at the time the action was performed, not based on the final outcome. The judge emphasised that in order to prove medical malpractice, three main elements must be fulfilled: negligence of professional standards, actual harm to the patient, and a direct causal relationship between the two. The criminal liability of doctors is ultimum remedium, so it can only be applied if there is proven gross negligence or intent that causes serious harm. This ruling strengthens legal certainty and protection for doctors who have acted in accordance with professional standards, while also providing legal guidelines for the protection of patients' rights.